2019
DOI: 10.1002/nbm.4193
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of artefactual MRS patterns from a large database using non‐negative matrix factorization

Abstract: This is the peer reviewed version of the following article: Hernández-Villegas, Y. [et al.]. Extraction of artefactual MRS patterns from a large database using non-negative matrix factorization. "NMR in biomedicine", 2 Desembre 2019, article e4193, p. 1-16, which has been published in final form at https://onlinelibrary.wiley.com/doi/abs/10.1002/nbm.4193. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Hernández‐Villegas et al 43 propose a convex nonnegative matrix factorization for the same multicenter studies used in Reference 41 to distinguish between good and poor quality spectra. The method first iteratively factorizes observations into a source matrix (of data centroids) and a mixing matrix (containing combination weights).…”
Section: Discussionmentioning
confidence: 99%
“…Hernández‐Villegas et al 43 propose a convex nonnegative matrix factorization for the same multicenter studies used in Reference 41 to distinguish between good and poor quality spectra. The method first iteratively factorizes observations into a source matrix (of data centroids) and a mixing matrix (containing combination weights).…”
Section: Discussionmentioning
confidence: 99%
“…Convergence was considered to be achieved when the reconstruction error of the signals was below the threshold value of 10 −5 . Given that in a previous study 18 we reported that the application of cNMF to a similar dataset often includes a variable number of sources that are either artifactual or very unstable, in this study we performed a previous robustness evaluation of the sources extracted. To this end, we extracted k = 2, 3, 4, 10, and 20 sources, and repeated each extraction 100 times.…”
Section: Methodsmentioning
confidence: 99%
“…The robustness of the set of solutions obtained decreased when increasing the number of sources, similarly to previous studies using the same approach. 18 For two and three sources, the same set was obtained in 100% of the repetitions. Beyond three sources, the solutions were exceedingly unstable.…”
Section: Source Extraction From Scer Spectramentioning
confidence: 99%
“…NMF and Convex-NMF are not new to the neuro-oncology domain, where they have been used to differentiate abnormal masses 19 ; to distinguish non-tumoral, responding and non-responding tumoral tissue in glioblastoma through source extraction in a semi-supervised way 20 ; for tumor type classification 21 ; or for spectral data quality control 22 , to name just a few applications.…”
Section: Convex-nmfmentioning
confidence: 99%